Speed variation analysis before and after the beginning of the stroke in swimming starts - Hubert, M.; Silveira, G. A.; Freitas, E.; Pereira, S.; Roesler, H. (Biomechanics and Medicine in Swimming X, 2006)
Currently, few biomechanics studies have been conducted to examine the transition from the underwater phase to the stroke phase in swimming Starts. The objective of this study was to evaluate the speed before and after the beginning of the stroke in front crawl and its relationship to the time to 15 meters in order to determine the importance of the underwater phase and transition phase in the entire performance of the swimmer. The transition speed of four athletes was recorded with video cameras and signal synchronizer. According to the results, the majority of swimmers reduced speed after the beginning of the stroke. There was a negative correlation between the difference in speed before and after commencing the stroke and the time at 15 meters. Therefore, attention should be paid to the underwater phase of Starts to improve performance in front crawl.